Penerapan Digital Marketing sebagai Strategi Pengembangan Usaha Ternak Tikus Putih - Candra Ahmadi; Dadang Hermawan; Srinadi N L P; Kusuma T M (Yumary: Jurnal Pengabdian kepada Masyarakat, 2021)
Purpose: This community service aimed to provide counseling on utilizing technological advances at the Bikul Bali White Rat Farm Business for marketing purposes. Method: Thee methods applied were accompaniment counseling on technological advances, lectures, and direct practice by applying digital marketing to reach and get new consumers. Result: The Partner understands the importance of implementing digital marketing and is confident in promoting their white rats through the marketplace even though there are extra costs for promotion. Conclusion: This community service activity has a positive impact as an additional knowledge of partners in understanding digital marketing. The partner now takes advantage of the availability of the marketplace as a medium for selling as a form of application of digital marketing and starting to reach new potential consumers who are accustomed to using marketplaces in shopping.